2012
DOI: 10.1007/s12031-012-9814-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease

Abstract: In this study, we investigated the protective role of silenced iNOS expression in neuron death in the nigrostriatal pathway in a 6-OHDA animal model of Parkinson's disease (PD). The animal model was established by intrastriatal infusion of a single dose of 6-OHDA. Silencing of iNOS expression was established by intrastriatal infusion of adenovirus-carried iNOS-targeted small interfering RNA (siRNA). Apomorphine-induced rotation behavior was measured. Expression of iNOS, OX-42, and TH; levels of DA, DOPAC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…The observed overexpression of iNOS PD skeletal muscles is consistent with the previous report [29] that skeletal muscle abnormalities in PD include inflammatory myopathies and myopathies associated with mitochondrial abnormalities. Upregulation of iNOS in PD skeletal muscles is also in agreement with the previous studies [43][44][45] reporting iNOS overexpression in other parkinsonian tissues including the brain, where iNOS upregulation has been suggested [46] as the cause of dopaminergic neuronal death leading to PD. Indeed, inhibition of nitric oxide synthase has been shown [45,47,48] to protect against MPTP-induced neurotoxicity in animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed overexpression of iNOS PD skeletal muscles is consistent with the previous report [29] that skeletal muscle abnormalities in PD include inflammatory myopathies and myopathies associated with mitochondrial abnormalities. Upregulation of iNOS in PD skeletal muscles is also in agreement with the previous studies [43][44][45] reporting iNOS overexpression in other parkinsonian tissues including the brain, where iNOS upregulation has been suggested [46] as the cause of dopaminergic neuronal death leading to PD. Indeed, inhibition of nitric oxide synthase has been shown [45,47,48] to protect against MPTP-induced neurotoxicity in animals.…”
Section: Discussionsupporting
confidence: 92%
“…Upregulation of iNOS in PD skeletal muscles is also in agreement with the previous studies [43][44][45] reporting iNOS overexpression in other parkinsonian tissues including the brain, where iNOS upregulation has been suggested [46] as the cause of dopaminergic neuronal death leading to PD. Indeed, inhibition of nitric oxide synthase has been shown [45,47,48] to protect against MPTP-induced neurotoxicity in animals. Therefore, reducing iNOS expression either pharmacologically [49,50], genetically [48,51], or by exercise as our finding indicated can protect various tissues in the different pathological conditions including PD.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, iNOS inhibition by siRNA or pharmacological inhibitors decreased protein radical formation. The neuroprotection by gene- silencing of iNOS in various models of Parkinson’s disease as shown by several investigators [2, 49] is possibly due to the role of iNOS in peroxynitrite-mediated protein radical formation. Under pathological conditions nitric oxide production results from transcriptional activation of iNOS, which is barely present in the healthy brain [49].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease is the second most common neurodegenerative disease of the aging brain and manifests itself mostly as a sporadic condition [1, 2]. Microglia-mediated neuroinflammation is considered to be a priming event in onset and progression of Parkinson’s disease [35].…”
Section: Introductionmentioning
confidence: 99%
“…16 Nonspecific iNOS inhibition could interfere with immune defense, but its role in the brain is more complex; one study indicated that mice lacking iNOS develop enhanced Alzheimers' pathology, 17 while others indicate that iNOS inhibition could actually be neuroprotective. 18 A more recent challenge has been designing inhibitors with high potency against human nNOS (hnNOS). Historically, many structure-based design efforts have utilized rat nNOS (rnNOS), so many compounds (such as most shown in Figure 1) are selective for the rat enzyme, leading to weaker hnNOS inhibitors with low selectivity over human eNOS (heNOS).…”
Section: Introductionmentioning
confidence: 99%